Effects of Video Modeling and Feedback on Mothers' Implementation of Peer‐to‐Peer Manding. (27th May 2015) - Madzharova, Maya S.; Sturmey, Peter
<x xml:space="preserve">Abstract</x> Children with autism spectrum disorder (ASD) exhibit deficits in appropriate requesting such as manding to peers. Experiment 1 used feedback and modeling to train three mothers to increase manding between three children with ASD and their typical siblings or peers. Video modeling and feedback increased the mother's correct implementation of the treatment but a causal relation was not established over the children's manding. Experiment 2 aimed to address the lack of functional control observed in the children's data using a partial component analysis. For one of the children there was a functional relation between the materials' location, which appeared to act as a motivating operation. When Sam's mother positioned the materials correctly his manding increased. These data indicated that a simple training protocol could be used to train caregivers to implement a complex social skill such as peer‐to‐peer interaction. Copyright © 2015 John Wiley & Sons, Ltd.